Opium use during pregnancy and infant size at birth: a cohort study - Siavash Maghsoudlou; Sven Cnattingius; Scott Montgomery; Mohsen Aarabi; Shahriar Semnani; Anna-Karin Wikström; Shahram Bahmanyar (BMC, 2018)
Abstract Background The reported positive association between opiatic drug use during pregnancy and adverse pregnancy outcomes might be confounded by other factors related to high-risk behaviors, including the use of other harmful substances. In rural areas of Iran, opium use during pregnancy is relatively common among women who otherwise do not have a hazardous lifestyle, which reduces the risk of residual confounding and increasing the possibility to identify its effects. We aimed to examine the association of antenatal exposure to opium with risks of small for gestational age, short birth length, and small head circumference at birth. Method In this cohort study in the rural area of the Golestan province, Iran, we randomly selected 920 women who were exposed to opium during pregnancy and 920 unexposed women during 2008-2010. Log-binomial regression was used to estimate risk ratios (RR) and 95% confidence intervals (CI) for the associations between prenatal exposure to opium and risks of small for gestational age, short birth length, and small head circumference at birth. Results Compared with non-use of opium and tobacco during pregnancy, using opium only and dual use of opium and tobacco were associated with increased risks of small for gestational age at births (RR = 1.71; 95% CI 1.34-2.18 and RR = 1.62; 95% CI 1.13-2.30, respectively). Compared with non-use of opium and tobacco, exposure to only opium or dual use of opium and tobacco were also associated with more than doubled increased risks of short birth length, and small head circumference in term infants. Conclusion Maternal opium use during pregnancy is associated with increased risks of giving birth to a small for gestational age infant, as well as a term infant with short birth length or small head circumference.